Architecting Cloud Native Applications : Design high-performing and cost-effective applications for the cloud /: Design high-performing and cost-effective applications for the cloud. (2019) - Arora, Kamal; Farr, Erik; Gilbert, John; Zonooz, Piyum
No abstract available